2015
DOI: 10.1002/bio.3071
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the effect of fluorescence quenching of bovine serum albumin by cefoxitin sodium using fluorescence spectroscopy and synchronous fluorescence spectroscopy

Abstract: The reaction mechanism of cefoxitin sodium with bovine serum albumin was investigated using fluorescence spectroscopy and synchronous fluorescence spectroscopy at different temperatures. The results showed that the change of binding constant of the synchronous fluorescence method with increasing temperature could be used to estimate the types of quenching mechanisms of drugs with protein and was consistent with one of fluorescence quenching method. In addition, the number of binding sites, type of interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In this study, the theoretical values k 2 = 2/3, n = 1.34, and Ф = 0.15 were collected from previously published concepts, 23,30 and the calculated areas from the curves of Figure 6 are listed in Table 5. The calculated average distances of these ligands from protein were observed below 7 nm, which indicated that the energy transfer occurred with a high possibility from BSA to drug molecules or their formed complex 8 . As temperature variation has not outright correlation on the nonradioactive energy transformation, 9 this study established the energy transfer profile at one temperature (298 K).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study, the theoretical values k 2 = 2/3, n = 1.34, and Ф = 0.15 were collected from previously published concepts, 23,30 and the calculated areas from the curves of Figure 6 are listed in Table 5. The calculated average distances of these ligands from protein were observed below 7 nm, which indicated that the energy transfer occurred with a high possibility from BSA to drug molecules or their formed complex 8 . As temperature variation has not outright correlation on the nonradioactive energy transformation, 9 this study established the energy transfer profile at one temperature (298 K).…”
Section: Resultsmentioning
confidence: 88%
“…The curves of the fluorescence spectrum of the bovine serum albumin and absorption spectrum of the ligand overlaid that indicated the higher possibility of the existence of energy transfer between donor and acceptor molecules from BSA to drug molecules or their formed complex. 8 As temperature variation has not outright correlation on the nonradioactive energy transformation, 9 this study established the energy transfer profile at one temperature (298 K). Moreover, it is vital to note here that the calculated distance between the protein and ligand (r) was larger than the value of critical distance (R 0 ) located at 50% energy transfer efficiency, which indicated the fluorescence quenching mechanism of the biomolecule was an obvious static process mediated by these three LG, linagliptin; RS, rabeprazole sodium.…”
Section: Energy Transfer Profilementioning
confidence: 99%
“…However, the quenching constants of static quenching decrease with the increase in temperature because of the instability of the complex . In order to further explore the fluorescence quenching mechanism of dinotefuran toward AtGPX6 at different temperatures, the Stern–Volmer linear equation was used to describe the fluorescence quenching data: In this equation, F 0 and F are the relative fluorescence intensities of AtGPX6 in the absence and presence of dinotefuran, respectively. K SV denotes the dynamic quenching constant, and [ Q ] is the concentration of dinotefuran.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction forces may be the weak interaction force, such as hydrogen bonding, van der Waals force, hydrophobic effect and electrostatic interaction, which are the main interactions between a small molecule and biological macromolecule. 52,53 The specic interactions can be determined based on the enthalpy change (DH) and entropy change (DS) in the…”
Section: Fluorescence Quenching Analysis and Binding Modementioning
confidence: 99%